Direct collapse to supermassive black hole seeds with radiation transfer: cosmological haloes. Issue 2 (22nd June 2018) - Ardaneh, Kazem; Luo, Yang; Shlosman, Isaac; Nagamine, Kentaro; Wise, John H; Begelman, Mitchell C
ABSTRACT: We have modelled direct collapse of a primordial gas within dark matter haloes in the presence of radiative transfer, in high-resolution zoom-in simulations in a cosmological framework, down to the formation of the photosphere and the central object. Radiative transfer has been implemented in the flux-limited diffusion (FLD) approximation. Adiabatic models were run for comparison. We find that ( a ) the FLD flow forms an irregular central structure and does not exhibit fragmentation, contrary to adiabatic flow which forms a thick disc, driving a pair of spiral shocks, subject to Kelvin–Helmholtz shear instability forming fragments; ( b ) the growing central core in the FLD flow quickly reaches 10 M_ and a highly variable luminosity of 10^38–10^39 erg s^-1, comparable to the Eddington luminosity. It experiences massive recurrent outflows driven by radiation force and thermal pressure gradients, which mix with the accretion flow and transfer the angular momentum outwards; and ( c ) the interplay between these processes and a massive accretion, results in photosphere at ∼10 au. We conclude that in the FLD model (1) the central object exhibits dynamically insignificant rotation and slower than adiabatic temperature rise with density; (2) does not experience fragmentation leading to star formation, thus promoting the fast track formation of a supermassive black hole (SMBH) seed; (3) inclusion of radiation force leads to outflows, resulting in the mass accumulation within the central 10 −3 pc, which is ∼100 times larger than characteristic scale of star formation. The inclusion of radiative transfer reveals complex early stages of formation and growth of the central structure in the direct collapse scenario of SMBH seed formation.